Short-coupled ventricular fibrillation represents a distinct phenotype among latent causes of unexplained cardiac arrest: a report from the CASPER registry. (19th May 2021) - Steinberg, Christian; Davies, Brianna; Mellor, Greg; Tadros, Rafik; Laksman, Zachary W; Roberts, Jason D; Green, Martin; Alqarawi, Wael; Angaran, Paul; Healey, Jeffrey; Sanatani, Shubhayan; Leather, Richard; et al.
Abstract: Aims : The term idiopathic ventricular fibrillation (IVF) describes survivors of unexplained cardiac arrest (UCA) without a specific diagnosis after clinical and genetic testing. Previous reports have described a subset of IVF individuals with ventricular arrhythmia initiated by short-coupled trigger premature ventricular contractions (PVCs) for which the term short-coupled ventricular fibrillation (SCVF) has been proposed. The aim of this article is to establish the phenotype and frequency of SCVF in a large cohort of UCA survivors. Methods and results : We performed a multicentre study including consecutive UCA survivors from the CASPER registry. Short-coupled ventricular fibrillation was defined as otherwise unexplained ventricular fibrillation initiated by a trigger PVC with a coupling interval of <350 ms. Among 364 UCA survivors, 24/364 (6.6%) met diagnostic criteria for SCVF. The diagnosis of SCVF was obtained in 19/24 (79%) individuals by documented ventricular fibrillation during follow-up. Ventricular arrhythmia was initiated by a mean PVC coupling interval of 274 ± 32 ms. Electrical storm occurred in 21% of SCVF probands but not in any UCA proband ( P < 0.001). The median time to recurrent ventricular arrhythmia in SCVF was 31 months. Recurrent ventricular fibrillation resulted in quinidine administration in 12/24 SCVF (50%) with excellent arrhythmia control. Conclusion : Short-coupled ventricular fibrillation is a distinct primary arrhythmia syndrome accounting for at least 6.6% of UCA. As documentation of ventricular fibrillation onset is necessary for the diagnosis, most cases are diagnosed at the time of recurrent arrhythmia, thus the true prevalence of SCVF remains still unknown. Quinidine is effective in SCVF and should be considered as first-line treatment for patients with recurrent episodes. Graphical Abstract: